2019
DOI: 10.2147/ijn.s193583
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ferumoxytol and CpG oligodeoxynucleotide 2395 synergistically enhance antitumor activity of macrophages against NSCLC with EGFR<sup>L858R/T790M</sup> mutation</p>

Abstract: Purpose: Drug resistance is a major challenge for epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) treatment of lung cancer. Ferumoxytol (FMT) drives macrophage (MΦ) transformation towards a M1-like phenotype and thereby inhibits tumor growth. CpG oligodeoxynucleotide 2395 (CpG), a toll-like receptor 9 (TLR9) agonist, is an effective therapeutic agent to induce anticancer immune responses. Herein, the effect of co-administered FMT and CpG on MΦ activation for treating non-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Macrophages exposed to poly(I:C)-nanocomplexes showed significant secretion of the T-cell attracting chemokines CXCL10 and CCL5 and improved ability to directly kill cancer cells [ 127 ]. Recently, the combination of CpG oligodeoxynucleotides (CpG; TLR9 agonist) with Ferumoxytol ® (FMT; an FDA approved drug for the treatment of iron deficiency) showed a synergistic antitumoral effect, mediated by an increased infiltration of M1-like macrophages (expressing F4/80 and iNOS) in a murine model of NSCLC [ 128 ]. A new hydrogel loaded with CpG and Doxorubicin showed also antitumoral efficacy, mediated by a decrease in M2-like TAMs and MDSCs, upon intratumoral implantation in a murine melanoma model [ 129 ].…”
Section: Tlr or Sting Signaling Activation To Reprogram Tamsmentioning
confidence: 99%
“…Macrophages exposed to poly(I:C)-nanocomplexes showed significant secretion of the T-cell attracting chemokines CXCL10 and CCL5 and improved ability to directly kill cancer cells [ 127 ]. Recently, the combination of CpG oligodeoxynucleotides (CpG; TLR9 agonist) with Ferumoxytol ® (FMT; an FDA approved drug for the treatment of iron deficiency) showed a synergistic antitumoral effect, mediated by an increased infiltration of M1-like macrophages (expressing F4/80 and iNOS) in a murine model of NSCLC [ 128 ]. A new hydrogel loaded with CpG and Doxorubicin showed also antitumoral efficacy, mediated by a decrease in M2-like TAMs and MDSCs, upon intratumoral implantation in a murine melanoma model [ 129 ].…”
Section: Tlr or Sting Signaling Activation To Reprogram Tamsmentioning
confidence: 99%
“…More recently, Wang et al demonstrated that ferumoxytol is primarily internalized by macrophages through scavenger receptors, i.e., SRI/II, and not mediated by complement C3b, as these rather large nanoparticles (30 nm) do not exhibit C3b deposition on their surface [ 174 ]. Taking another approach, Wang et al proved that the intracellular TLR9-agonists CpG and ferumoxytol also synergize to promote an M1-like phenotype in macrophages with anti-tumoricidal capacity [ 175 ]. While the results outlined thus far are mainly focused on the synergy between IONPs and TLR agonists, others have demonstrated that the pro-M1/anti-tumor properties of ferumoxytol are intrinsic to the NP.…”
Section: Ionp Effects Is Dependent On Cell Type and Statusmentioning
confidence: 99%
“…[1,19] In previous studies, ferumoxytol (Feraheme, Rienso), a formulation of an iron oxide nanoparticle in a matrix of covalently crosslinked carbohydrates (polyglucose sorbitol carboxymethylether), was used as iron source. [19][20][21][22][23] Despite its approval for the treatment of iron deficiency anemia in patients with chronic kidney disease, the original intention of ferumoxytol was as a contrast agent for magnetic resonance imaging designed for minimal iron release. [24][25][26][27][28][29][30] We now propose that delivery systems which allow for controlled iron release in the TME can serve as immunotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%